2018
DOI: 10.5194/cp-2018-121
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mercury anomalies across the Palaeocene-Eocene Thermal Maximum

Abstract: Abstract. Large-scale magmatic events like the emplacement of the North Atlantic Igneous Province (NAIP) are often coincident with periods of extreme climate change such as the Palaeocene–Eocene Thermal Maximum (PETM). One proxy for volcanism in the geological record that is receiving increased attention is the use of mercury (Hg) anomalies. Volcanic eruptions are among the dominant natural sources of Hg to the environment; thus, elevated Hg/TOC values in the sedimentary rock record may reflect an increase in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(45 citation statements)
references
References 97 publications
(175 reference statements)
4
41
0
Order By: Relevance
“…Two further Hg excursions to 30 and 20 ppb are also present above the P‐E boundary at Blake Nose. TOC contents from the Blake Nose samples are generally too low (<0.2 wt%) to yield reliable Hg/TOC ratios [see Jones et al, ]. An elevation in Hg at the base of and within the main body of the PETM CIE is broadly consistent with previous investigations, although individual sedimentary records appear to show different patterns of these enrichments (Jones et al, ; Keller et al, ).…”
Section: Resultssupporting
confidence: 68%
See 4 more Smart Citations
“…Two further Hg excursions to 30 and 20 ppb are also present above the P‐E boundary at Blake Nose. TOC contents from the Blake Nose samples are generally too low (<0.2 wt%) to yield reliable Hg/TOC ratios [see Jones et al, ]. An elevation in Hg at the base of and within the main body of the PETM CIE is broadly consistent with previous investigations, although individual sedimentary records appear to show different patterns of these enrichments (Jones et al, ; Keller et al, ).…”
Section: Resultssupporting
confidence: 68%
“…TOC contents from the Blake Nose samples are generally too low (<0.2 wt%) to yield reliable Hg/TOC ratios [see Jones et al, ]. An elevation in Hg at the base of and within the main body of the PETM CIE is broadly consistent with previous investigations, although individual sedimentary records appear to show different patterns of these enrichments (Jones et al, ; Keller et al, ). Recent studies indicated that Hg enrichments could also be associated with increased sulfur/pyrite contents in highly reducing conditions (Shen et al, ).…”
Section: Resultssupporting
confidence: 68%
See 3 more Smart Citations